A Modern History of the Kurds, 3d rev. ed.: By David McDowall (London and New York: I.B. Tauris, 2005. 515 pages.) (American Journal of Islam and Society, 2006)
This extensive survey of the Kurds’ history is divided into five sections:“The Kurds in the Age of Tribe and Empire,” “Incorporating the Kurds,”“Ethno-nationalism in Iran,” “Ethno-nationalism in Iraq,” and “Ethnonationalismin Turkey.” An introduction on Kurdish identity and social formation, as well as four appendices discussing the Treaty of Sèvres and theKurds of Syria, Lebanon, and Caucasia, are also included. David McDowall,a noted British specialist on Middle Eastern minority affairs and anacknowledged expert on Kurdish studies, has extensively revised the 1996second edition of his book. He provides an analysis of recent Kurdish eventsand a more up-to-date bibliography at the end of each section.This highly detailed history begins in the nineteenth century and ends inthe present day. The author discusses the interplay of the old and new facetsof Kurdish politics: local rivalries within Kurdish society; the enduringauthority of the traditional leadership represented by sheikhs and aghas; thefailure of modern nation states to respond to the challenge of Kurdishnationalism; and the use of Kurdish groups as pawns by major western powersand regional states in the region’s power politics. His methodology is primarilypolitical-historical in nature; however, anthropological and socialanalysis are not totally lacking.As presented by McDowall, a close scrutiny of modern Kurdish historyreveals striking continuities. For example, one pattern has characterizedKurdish-Iraqi relations since 1958: Each Iraqi government pursued peacenegotiations with the Kurds at first, only to fight them when it felt secureabout its rule. This pattern is also found in Iran’s relations with its Kurds.Turkey, however, has pursued a policy that seeks to assimilate and, at times,even ethnically cleanse its Kurdish population.There is also continuity in the major powers’ manipulation of the“Kurdish card” in Iraq. McDowall writes that in 1976, the SelectIntelligence Committee of the House of Representatives reported to theHouse that neither Iran nor the United States would like to see the civil wargoing on in Iraq at that time resolved in a way that would give the Kurds aclear win. Twenty years later, in 1991, the United States implemented a similarpolicy with the Kurds’ so-called “exclusionary zone’’ in northern Iraq.Fearing the consequences likely to follow Saddam Hussein’s overthrow – inparticular, the dismemberment of Iraq and wider regional instability – theUnited States refused to give the Kurds sufficient aid to enable them toestablish an independent homeland ...